1992
DOI: 10.1159/000247429
|View full text |Cite
|
Sign up to set email alerts
|

Acral Persistent Papular Mucinosis and IgA Monoclonal Gammopathy: Report of a Case

Abstract: The case of a 60-year-old man with acral persistent papular mucinosis (APPM), thought to represent a new distinctive form of dermal mucinosis not associated with systemic diseases, is reported. The patient had a 4-year history of multiple small papular lesions on the distal forearms, wrists and back of the hands. Histologically, mucin deposits in the upper and mid dermis sparing a superficial sub-epidermal grenz zone were observed. In contrast to previously described cases, a monoclonal IgA of k light chain is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Based on clinicopathologic evidence and specificity, APPM was listed as its own entity, unassociated with lichen myxedematosus or DPLM. However, in 1992 Borradori et al 10 reported an unequivocal case of APPM with the unique finding of an IgA monoclonal gammopathy of kappa light chain isotype. An IgG monoclonal gammopathy is a requirement for the diagnosis of scleromyxedema, the generalized form of lichen myxedematosus.…”
Section: Discussionmentioning
confidence: 99%
“…Based on clinicopathologic evidence and specificity, APPM was listed as its own entity, unassociated with lichen myxedematosus or DPLM. However, in 1992 Borradori et al 10 reported an unequivocal case of APPM with the unique finding of an IgA monoclonal gammopathy of kappa light chain isotype. An IgG monoclonal gammopathy is a requirement for the diagnosis of scleromyxedema, the generalized form of lichen myxedematosus.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Topical corticosteroids, tacrolimus, [8] and pimecrolimus have been used with some success, [22,24] although more studies are required to show the benefit of various treatments. [2] Topical and intralesional corticosteroids have been used with variable success [16,22,25] often without response, [20] and resolved lesions may also recur after corticosteroids are stopped. [25] Spontaneous resolution may occur in LM [3,26] including discrete papular mucinosis, [3] but no tendency to spontaneous resolution was previously reported in APPM, [13][14][15] even after four [27] or twelve years [3] of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Topical and intralesional corticosteroids have been used with variable success [16,22,25] often without response, [20] and resolved lesions may also recur after corticosteroids are stopped. [25] Spontaneous resolution may occur in LM [3,26] including discrete papular mucinosis, [3] but no tendency to spontaneous resolution was previously reported in APPM, [13][14][15] even after four [27] or twelve years [3] of follow-up. Our patient was not given any treatment and was counselled regarding only cosmetic effect of disease with no systemic involvement and the lesions were asymptomatic and not very apparent.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by multiple, asymptomatic, skin‐coloured to ivory papules, 2–5 mm in size, distributed on the dorsal hands, wrists and forearms. Histologically, it is defined by focal deposits of mucin in the papillary and mid‐dermis with sparing of a Grenz zone 2 …”
Section: Discussionmentioning
confidence: 99%